The Counteracting Effect of Chrysin on Dietary Fructose-Induced Metabolic-Associated Fatty Liver Disease (MAFLD) in Rats with a Focus on Glucose and Lipid Metabolism - Gabriela Campanher; Nelson Andrade; Joanne Lopes; Cláudia Silva; Maria João Pena; Ilda Rodrigues; Fátima Martel (Molecules)
The prevalence of metabolic syndrome has been exponentially increasing in recent decades. Thus, there is an increasing need for affordable and natural interventions for this disorder. We explored the effect of chrysin, a dietary polyphenol, on hepatic lipid and glycogen accumulation, metabolic dysfunction-associated fatty liver disease (MAFLD) activity score and oxidative stress and on hepatic and adipose tissue metabolism in rats presenting metabolic syndrome-associated conditions. Rats fed a chow diet were separated into four groups: Control (tap water), Fructose (tap water with 10% fructose), Chrysin (tap water+ chrysin (100 mg/kg body weight/d)), and Fructose + Chrysin (tap water with 10% fructose + chrysin (100 mg/kg body weight/d, daily)) (for 18 weeks). When associated with the chow diet, chrysin reduced hepatic lipid and glycogen storage, increased the hepatic antioxidant potential of glutathione and reduced de novo lipogenesis in the adipose tissue. When associated with the high fructose-diet, chrysin attenuated the increase in lipid and glycogen hepatic storage, improved the MAFLD activity score, decreased hepatic lipid peroxidation, increased the antioxidant potential of glutathione, and improved lipid and glucose metabolic markers in the liver and adipose tissue. In conclusion, our results suggest that chrysin is a beneficial addition to a daily diet for improvement of hepatic metabolic health, particularly for individuals suffering from metabolic syndrome.